Challenges Faced by EFL Students in Academic Oral Presentations: A Focus on Speaking Anxiety - Moch. Nur Cholis Majid; Nur Mukminatien; Maria Hidayati (Yayasan Payungi Smart Madani, 2025)
Academic oral presentation is a fundamental component of higher education, particularly for EFL students who are required to communicate academic content in a foreign language. However, many EFL learners experience substantial difficulties when performing academic oral presentations. This study aims to investigate the challenges encountered by EFL students in delivering academic oral presentations, with a particular focus on speaking anxiety. Employing a descriptive quantitative research design, data were collected from undergraduate EFL students through a self-administered questionnaire measuring emotional, cognitive, social-evaluative, and physiological dimensions of speaking anxiety. The data were analyzed using descriptive statistical techniques to identify dominant patterns of challenges experienced by the students. The findings reveal that EFL students face multifaceted challenges during academic oral presentations, with emotional and social-evaluative anxiety emerging as the most prominent difficulties. Cognitive disruptions, such as mental blocks and difficulty organizing ideas, as well as physiological symptoms, were also commonly reported. These results indicate that speaking anxiety in academic oral presentations is a multidimensional phenomenon influenced by the evaluative nature of academic contexts. The study emphasizes the importance of addressing affective factors in conjunction with linguistic competence in academic speaking instruction, and it provides pedagogical implications for creating supportive presentation environments in EFL higher education contexts. Keywords: English as a foreign language, academic speaking, oral presentation anxiety, university students, EFL context